Effects of dietary potato by-product and rumen-protected histidine on growth, carcass characteristics and quality attributes of beef. (September 2015) - Thornton, K.J.; Richard, R.P.; Colle, M.J.; Doumit, M.E.; de Veth, M.J.; Hunt, C.W.; Murdoch, G.K.
Abstract: We hypothesized that variable composition in finishing rations, more specifically; the proportion of potato-by-product (PBP) and rumen protected histidine (His) supplementation may influence growth and meat quality attributes. Two different diets were fed (1) finishing ration with corn and barley as grains (CB, n = 20) and (2) substitution of 10% corn, DM basis, with PBP (PBP, n = 20). Additionally, half of each dietary treatment received 50 g/hd/d rumen protected His (HS, n = 20) while the other half received no supplement (NS, n = 20). Inclusion of 10% PBP or HS did not affect growth or carcass traits. Color stability was analyzed using Hunter color values as well as AMSA visual appraisal in both longissimus thoracis (LT) and gluteus medius (GM) muscles. The LT, but not the GM, of CB steers was more color stable over a 9 d simulated retail display compared to those fed a PB diet. Steers receiving HS produced significantly ( P  < 0.05) more color stable LT and GM steaks. Highlights: Steers were fed rumen protected histidine; growth and meat quality were analyzed. Steers were fed potato-by-product; growth and meat quality were analyzed. Including histidine in finishing ration significantly improved meat color stability. Feeding potato by-product decreased color stability of end products. Results may improve our understanding of color stability in beef products.